2010
DOI: 10.1590/s1678-77572010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Luting glass ceramic restorations using a self-adhesive resin cement under different dentin conditions

Abstract: ObjectivesThe aim of this study was to investigate the bond strength of ceramic restorations luted using a self-adhesive resin cement (RelyX Unicem, 3M ESPE) under different dentin conditions.Material and MethodsIn the experimental groups, ceramic restorations were luted to bovine incisors with RelyX Unicem under the following conditions: [Dry dentin]: surface was dried using air stream for 15 s; [Moist dentin]: excess dentin moisture was removed with absorbent paper; [Bonding agent]: Clearfil SE Bond (Kuraray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 16 publications
(17 reference statements)
1
26
1
5
Order By: Relevance
“…These values were higher than those obtained by Piwowarczyk et al 14 11 Sarr et al, 19 Luhrs et al, 20 Mazzitelli et al, 21 Ebert et al, 22 and Inukai et al 23 Although the hydrated dentin substrate can facilitate ionization of the acid monomers, the results of this study suggested that the humidity conditions did not affect the bond strength of RelyX Unicem to dentin, i.e., no significant difference was observed when the self-adhesive was applied to surfaces with different humidity conditions. Conversely, when Guarda et al 24 did not over-dry the dentin surface before cementation, a higher bond strength was observed for RelyX Unicem. Moreover, Mazzitelli et al 21 found that RelyX Unicem performed better under simulated pulpar pressure, because the constant intrapulpar water perfusion changes the substrate wetness.…”
Section: Discussionmentioning
confidence: 90%
“…These values were higher than those obtained by Piwowarczyk et al 14 11 Sarr et al, 19 Luhrs et al, 20 Mazzitelli et al, 21 Ebert et al, 22 and Inukai et al 23 Although the hydrated dentin substrate can facilitate ionization of the acid monomers, the results of this study suggested that the humidity conditions did not affect the bond strength of RelyX Unicem to dentin, i.e., no significant difference was observed when the self-adhesive was applied to surfaces with different humidity conditions. Conversely, when Guarda et al 24 did not over-dry the dentin surface before cementation, a higher bond strength was observed for RelyX Unicem. Moreover, Mazzitelli et al 21 found that RelyX Unicem performed better under simulated pulpar pressure, because the constant intrapulpar water perfusion changes the substrate wetness.…”
Section: Discussionmentioning
confidence: 90%
“…The filler particles in the U200 group were dispersed and protruded in the resin matrix ( Figure 1B) compared to the surfaces in the ARC group, which were smooth and regular ( Figure 2B). The self-etching luting cements had amounts of water generated during neutralization of the functional groups modified by phosphoric acid that were reused to react with acidic functional groups 9 . It is likely that the water generated during the setting reaction contributed to the erosive degradation in the U200 group, leading to greater %VHN than in the ARC group (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…However, the composition of the luting cements can influence its degradation in an acidic environment 6,7 . The luting cements available can be classified as water-based and resin-based cements [8][9][10] . The most commonly used water-based luting agents are zinc phosphate and glass-ionomer cements 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bonding of ceramics according to cementation strategy Self-adhesive resin cements, which consist almost exclusively of zirconium oxide-based ceramics, contain phosphate monomers that chemically bond to zirconium and may exhibit higher bond strength values after sandblasting with aluminum oxide when compared to conventional cements 14 . Furthermore, selfadhesive resin cements have the advantage of needing no bonding agent or other pre-treatment of the tooth, in addition to reducing post-cementing sensitivity 14 .…”
Section: Conclusãomentioning
confidence: 99%